Revolusi dan Kontinuitas:Membahas Warisan Budaya Bani Umayyah dalam Konteks Dunia Modern - Noor Hidayah (PT. Banjarese Pacific Indonesia, 2024)
The Umayyad dynasty which rule from 661 AD from 750 AD,stands as a pivotal period in early islamic history leaving a diverse and influential cultural legacy that persists into the modern era .This research aims to explore how to the cultural heritage of the umayyads remains relevant of the context modern world,particularly in the fields of art and architecture.The Umayyad dynasty is renowned for estabilishing a strong empire that encompassed vast territories from the Middle East to Andalusia in Spain.Calliph Abdul Malik ibn Marwan , a prominent figure of the time,introduced the Umayyad Dinar as the official currency and initiated the monumental project Dome of The Rock in Jerusalem,which continues to be one of the most significant symbols of Islamic architecture.Umayyad architeture reflects a blend of Roman, Persian , and newly introduced islamic elements.Their distinctive of domes, calligraphy,and intricate mosaics has deeply inspired modern artists and architect. This study explores how the cultural values from the past continue to inspire and shape contemporary works.By considering the global impact of Umayyad heritage, we can understand how continuity and evolution in human history occur through the development of art,architecture and values systems.Through this analysis, we highlight the importance of understanding how cultural values from the past can reinterpreted in different contexts to support the evolution of an inclusive and sustainable cultural future.